Sistem Informasi Inventaris Barang Berbasis Web pada Satker Bid TIK Polda Gorontalo - Desi A Yusuf; Wahyudin Hasyim; Hilmansyah Gani; Frangky Tupamahu (Prodi Teknik Informatika Universitas Pasir Pengaraian, 2026)
Inventory management is an important activity in supporting the operational performance of an organization. At the Information and Communication Technology Division (Bid TIK) of the Gorontalo Regional Police, inventory management is still carried out manually using spreadsheets, resulting in several problems such as recording errors, data duplication, difficulties in retrieving item information, and delays in report preparation. This study aims to design and develop a web-based Inventory Information System (SIMBAR) to improve the effectiveness and efficiency of inventory management. The system was developed using the Waterfall method, which consists of requirements analysis, system design, implementation, testing, and maintenance stages. PHP was used as the programming language, while MySQL served as the database management system. The developed system provides features for inventory data management, incoming and outgoing goods transactions, asset borrowing and returning, stock monitoring, and inventory reporting. System testing was conducted using the Black Box Testing method to ensure that all system functions operated according to user requirements. The testing results showed that all system modules achieved a valid status based on Black Box Testing. The results of this study indicate that the system improves the accuracy of inventory data management, accelerates data recording and retrieval processes, facilitates real-time stock monitoring, and speeds up inventory report generation. Therefore, the developed system can support a more effective, efficient, and integrated inventory management process at the Information and Communication Technology Division (Bid TIK) of the Gorontalo Regional Police.